The effect of high-intensity interval training on health-related outcomes in obese adolescents: a systematic review and meta-analysis - Xu, Gang; Li, Qiang; Yang, Qian; Yu, Hongli (Frontiers in Physiology, 2025)
ObjectiveThe present research was to evaluate the impacts of high-intensity interval training (HIIT) intervention on health-related outcomes in obese adolescents, adopting a systematic review and meta-analysis.MethodologyThe study was performed by searching four databases (PubMed, Web of Science, Embase, and Cochrane Library) to determine randomized controlled trials (RCTs) exploring the impacts of HIIT to physiological parameters among obese adolescents. The sequential execution of a meta-analyses, subgroup analyses, and publication bias analyses was accomplished utilizing the software package RevMan version 5.4 and Stata 18.ResultsThere were 11 articles included. This research demonstrated a significant impact on body fat percentage (BFP) with d = −0.82, P < 0.05; VO2peak with d = 2.99, P < 0.05; high density lipoprotein (HDL) with I2 = 22.8%, SMD = 0.47, 95% CI [0.06 to 0.88]; systolic blood pressure (SBP) with I2 = 0.3%, SMD = −0.93, 95% CI [−1.25 to −0.62]. However, there was lacking of significance of body mass index (BMI) d = −0.21, P = 0. The subgroup analyses revealed that HIIT interventions involving with twice per week, 30–60 min per session, 1–30 min per session were the most effective in improving BMI, BFP and VO2peak.ConclusionHIIT intervention, its impact on BMI is minimal, HIIT significantly reduces BFP, enhances VO2peak, increases HDL levels, and lowers SBP. HIIT effectively enhances body composition and cardiovascular health in overweight adolescents. Future studies should aim to refine HIIT protocols and explore its long-term benefits to establish comprehensive exercise recommendations for this population.Systematic Review Registrationidentifier CRD42025630480.